Zakat dalam Model Ekonomi Makro (Solusi Ketimpangan dan Pertumbuhan Ekonomi) - Heryanto Heryanto (Trunojoyo University of Madura, 2020)
This study aims to explore and evaluate the effectiveness of zakat distribution as a mechanism for alleviating the poor. The approach used in this study is the study of literature or library research. The results of this study indicate that the effect of zakat distribution on efforts to reduce poverty is varied in each region. Even so, the distribution of zakat funds has a positive effect, but the influence of zakat is varied. There is even a small impact on increasing the income of the poor and economic growth. This is caused by different perspectives in various regions. Therefore, the management of zakat needs to be adjusted with the recipient's profile of zakat (mustahik). Within the national (macroeconomic) framework, zakat funds can be used to increase the purchasing power of the poor and economic growth, thereby narrowing the gap between rich and poor people. In general, muzaki and mustahik have the same view on the aspect of zakat, namely as an activity of worship.